Emissao de oxido xitroso em solos com diferentes usos e manejos: Uma revisao - De Almeida, Risely Ferraz [UNESP]; Naves, Emmanuel Rezende; Silveira, Camila Haddad [UNESP]; Wendling, Beno [UNESP] (Centro Universitario de Maringa, 2015)
Agriculture is one of the main emitter of nitrous oxide (N,OK one of die gases that cause the greenhouse effect in the atmosphere. The management system and soil usage in agriculture affects the gas flow. The soil affects the nitrogen cycle through the availability of nitrate, temperature. pH. moisture. NH4 (ammonia ion) and content of oxidizing compounds used as electron receivers for the degradation of the soil's organic matter. The dominating factor, within the above soil conditions, which regulate the formation and emission of nitrous oxide, is the porous space occupied by water (PSW) coupled to temperature. Aerated soil with PSW between 35 and 60% form nitrous oxide as a byproduct of nitrification. Within the culture systems used in Brazil, no- Till farming and conventional farming still require further studies to verify their influence on the production process and emission of nitrous oxide from soils. Research works on greenhouse gases must be further undertaken at different managements and usages of soil in agriculture. Correct alternatives are required to lessen their emission into the atmosphere.
The emission of nitrous oxide in soils with different usages and managements: A review
Keywords: Agriculture; Atmosphere; Greenhouse gases; Nitrogen